logo

Matrix Projection in Linear Algebra 📂Matrix Algebra

Matrix Projection in Linear Algebra

Definition

A square matrix PCm×mP \in \mathbb{C}^{m \times m} is a projector if P2=PP^2 = P.

Explanation

In algebraic terms, this is referred to as an idempotent, which similarly refers to an element like a2=aa^2 = a.

If PP is a projection, then (IP)2=I2P+P2=I2P+P=(IP)(I-P)^2 = I - 2P + P^2 = I - 2P + P = (I-P), so it can be known that (IP)(I-P) is also a projection.

Such a projector (IP)(I - P) is called the complementary projector of PP.

Thinking of projection as a linear transformation geometrically, it’s like casting light on a geometric figure and obtaining its shadow. For example, a function like f(x,y,z):=(x,y,0)f(x,y,z) := (x,y,0) shoots light towards the direction of the zz axis and represents the shadow that forms on the xyxy plane. Projecting the shadow again yields the same result, hence the definition of P2=PP^2 = P as a projector is sensible.

Properties

Projection PCm×mP \in \mathbb{C}^{m \times m} and its complementary projection IPI-P satisfy the following properties:

(a) C(IP)=N(P)\mathcal{C} (I-P) = \mathcal{N} (P)

(b) N(1P)=C(P)\mathcal{N} (1-P) = \mathcal{C} (P)

(c) N(1P)N(P)={0}\mathcal{N} (1-P) \cap \mathcal{N} (P) = \left\{ 0 \right\}

(d) C(P)N(P)={0}\mathcal{C} (P) \cap \mathcal{N} (P) = \left\{ 0 \right\}

(e) C(P)N(P)=Cm\mathcal{C} (P) \oplus \mathcal{N} (P) = \mathbb{C}^{m}

Proof

(a)(b)

It suffices to show that C(IP)\mathcal{C} ( I - P) and N(P)\mathcal{N}(P) are inclusive of each other. For any vector vCm\mathbf{v} \in \mathbb{C}^{m},

(IP)v=vPv (I - P) \mathbf{v} = \mathbf{v} - P \mathbf{v}

If vN(P)\mathbf{v} \in \mathcal{N} (P), then Pv=0P \mathbf{v} = \mathbb{0}, hence (IP)v=v(I - P) \mathbf{v} = \mathbf{v}, i.e., vC(IP)\mathbf{v} \in \mathcal{C} (I - P), thus

N(P)C(IP) \mathcal{N} (P) \subset \mathcal{C} (I - P)

If we let wC(IP)\mathbf{w} \in \mathcal{C} (I-P), then any v\mathbf{v} satisfying w=(IP)v\mathbf{w} = (I - P) \mathbf{v} is also in C(IP)\mathcal{C} (I-P). Taking the projection PP on w=(IP)v\mathbf{w} = (I - P) \mathbf{v},

Pw=PvP2v=PvPv=0 P \mathbf{w} = P \mathbf{v} - P^2 \mathbf{v} = P \mathbf{v} - P \mathbf{v} = \mathbb{0}

Thus wN(P)\mathbf{w} \in \mathcal{N} (P), and therefore

C(IP)N(P) \mathcal{C} (I - P) \subset \mathcal{N} (P)

Hence (1) is proven, and since P=I(IP)P = I - (I- P), by regarding the complementary projection (IP)(I - P) of projection PP, (2) is immediately proven.

(c)(d)

Assume that vN(IP)N(P)\mathbf{v} \in \mathcal{N} (I - P) \cap \mathcal{N} (P) is not the zero vector. However, since vN(IP)\mathbf{v} \in \mathcal{N} (I - P), (IP)v=0(I-P) \mathbf{v} = \mathbb{0}, and vN(P)\mathbf{v} \in \mathcal{N} (P),

Pv=0 P \mathbf{v} = \mathbb{0}

Adding both sides yields (IP)v+Pv=v=0(I-P) \mathbf{v} + P \mathbf{v} = \mathbf{v} = \mathbb{0}, which is a contradiction to the assumption.

Thus, (3) is proven, and (4) is immediately proven by (1) and (2).

(e)

By the definition of direct sum, it suffices to show existence, exclusivity, and uniqueness.

  • (i) Existence

    By (a), N(P)=C(IP)\mathcal{N} (P) = \mathcal{C} (I - P), and for any vector sCm\mathbf{s} \in \mathbb{C}^{m}, PsC(P)P \mathbf{s} \in \mathcal{C}(P), and (IP)sC(IP)(I - P)\mathbf{s} \in \mathcal{C} (I - P).

However, since Ps+(IP)s=Ps+sPs=sCmP \mathbf{s} + (I - P) \mathbf{s} = P \mathbf{s} + \mathbf{s} - P \mathbf{s} = s \in \mathbb{C}^{m}, s\mathbf{s} can always be represented as the sum of C(P)\mathcal{C}(P) and C(IP)\mathcal{C} (I - P).

  • (ii) Exclusivity

    Already proven in (d).

  • (iii) Uniqueness

    From the above (ii), for sCms \in \mathbb{C}^{m},

    s=c1+n1=c2+n2 \mathbf{s} = \mathbf{c}_{1} + \mathbf{n}_{1} = \mathbf{c}_{2} + \mathbf{n}_{2}

    There exist c1,c2C(P)\mathbf{c}_{1} , \mathbf{c}_{2} \in \mathcal{C}(P) and n1,n2N(P)\mathbf{n}_{1}, \mathbf{n}_{2} \in \mathcal{N}(P) satisfying it.

Let’s assume c1c2\mathbf{c}_{1} \ne \mathbf{c}_{2} and n1n2\mathbf{n}_{1} \ne \mathbf{n}_{2}.

Multiplying both sides of c1+n1=c2+n2\mathbf{c}_{1} + \mathbf{n}_{1} = \mathbf{c}_{2} + \mathbf{n}_{2} by PP,

Pc1+Pn1=Pc2+Pn2 P\mathbf{c}_{1} + P\mathbf{n}_{1} = P\mathbf{c}_{2} + P\mathbf{n}_{2}

Meanwhile, since n1,n2N(P)\mathbf{n}_{1}, \mathbf{n}_{2} \in \mathcal{N} (P),

Pc1=Pc2 P\mathbf{c}_{1} = P\mathbf{c}_{2}

Thus P(c1c2)=0P( \mathbf{c}_{1} - \mathbf{c}_{2} ) = \mathbb{0}. By the definition of the null space, (c1c2)N(P)( \mathbf{c}_{1} - \mathbf{c}_{2}) \in \mathcal{N}(P), and by the property of vector spaces, (c1c2)C(P)( \mathbf{c}_{1} - \mathbf{c}_{2}) \in \mathcal{C}(P), which by (exclusivity) must mean c1c2=0\mathbf{c}_{1} - \mathbf{c}_{2} = \mathbb{0}.

This contradicts the assumption c1c2\mathbf{c}_{1} \ne \mathbf{c}_{2}, and similarly, n1=n2\mathbf{n}_{1} = \mathbf{n}_{2} being true can be shown.

See also